Representation of the Identity of the Indonesian Ulama Council in Fatwa Regarding Religious Blasphemy in the Case of Basuki Tjahaja Cahaya Purnama (Ahok) - Mery Kharismawati; Arief Hidayat (Public Knowledge, 2024)
MUI's fatwa in the case of blasphemy and insulting clerics by Ahok is a complex event. It not only signifies the rise of political Islam in the arena of contestation but also symbolizes the presence of identity representation. MUI through its fatwa seems to confirm the presence of sectarian identity based on religion. This refers to Johnson's concept that the media text leads to something behind it. By analyzing the fatwa, it becomes clear that through its text, MUI not only shows itself as an affirmation of Islamic identity as the dominant but also as a binary differentiator in the cultural representation of Indonesian society in various other dimensions. By using a text analysis approach and also a literature study, the author concluded that MUI has opened political identity in the electoral arena. The issuance of MUI fatwa text in Ahok's case has opened a new level of cultural representation dynamics, through religious identity that goes hand in hand with electoral contestation.